2022
DOI: 10.1186/s12984-022-01012-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of step frequency during running on the magnitude and symmetry of ground reaction forces in individuals with a transfemoral amputation

Abstract: Background Individuals with unilateral transfemoral amputation are prone to developing health conditions such as knee osteoarthritis, caused by additional loading on the intact limb. Such individuals who can run again may be at higher risk due to higher ground reaction forces (GRFs) as well as asymmetric gait patterns. The two aims of this study were to investigate manipulating step frequency as a method to reduce GRFs and its effect on asymmetric gait patterns in individuals with unilateral tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…As suggested, a lower t c reduces the window in which the running direction deviates from the intended direction. Additionally, a higher step frequency has been shown to reduce the magnitude of the GRF during loading, which is beneficial for alleviating the risk of bone and muscle overuse injuries 32 . Therefore, improving step frequency might holistically improve running performance, including the ability to maintain a straight movement path and faster running speed.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested, a lower t c reduces the window in which the running direction deviates from the intended direction. Additionally, a higher step frequency has been shown to reduce the magnitude of the GRF during loading, which is beneficial for alleviating the risk of bone and muscle overuse injuries 32 . Therefore, improving step frequency might holistically improve running performance, including the ability to maintain a straight movement path and faster running speed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Paralympic athletes exhibit greater asymmetry compared to conventional athletes, particularly in impairments that have unilateral relationships [ 6 , 7 , 8 ]. However, there are studies reporting that the type of disability, and their possible asymmetries, would not affect the result [ 9 ].…”
Section: Introductionmentioning
confidence: 99%